Ebola-specific therapeutic antibodies from lab to clinic: The example of ZMapp - Wong, Gary; Bienes, Kathrina Mae; XIII, Ara; Fausther-Bovendo, Hugues; Kobinger, Gary P. (Antiviral research, 2024)
In the 1990s, monoclonal antibodies (mAbs) progressed from scientific tools to advanced therapeutics, particularly for the treatment of cancers and autoimmune and inflammatory disorders. In the arena of infectious disease, the inauguration of mAbs as a post-exposure treatment in humans against Ebola virus (EBOV) occurred in response to the 2013–2016 West Africa outbreak. This review recounts the history of a candidate mAb treatment, ZMapp, beginning with its emergency use in the 2013–2016 outbreak and advancing to randomized controlled trials into the 2018–2020 African outbreak. We end with a brief discussion of the hurdles and promise toward mAb therapeutic use against infectious disease.